Comparison of external beam radiation and brachytherapy to external beam radiation alone for unresectable extrahepatic cholangiocarcinoma - Boothe, Dustin; Hopkins, Zachary; Frandsen, Jonathan; Lloyd, Shane (Journal of Gastrointestinal Oncology; Vol 7, No 4 (August 01, 2016): Journal of Gastrointestinal Oncology, 2016)
Background: Extrahepatic cholangiocarcinoma (EHC) is a rare malignancy with a relatively poor prognosis. There are no randomized, prospective data to help define the optimal method of radiation delivery for unresectable EHC. The purpose of this study was to evaluate the benefit of adding brachytherapy to external beam radiation therapy (EBRT) for unresectable EHC. Methods: A retrospective review of 1,326 patients with unresectable EHC using the Surveillance, Epidemiology, and End Results (SEER) database was completed. Kaplan-Meier methods were used to analyze the primary endpoint, overall survival. Univariate and multivariate analysis was performed to identify and control for potential confounding variables, including age at diagnosis, sex, stage, grade, histology, race, year of diagnosis, and reason for no surgery. Results: Of the 1,326 patients with unresectable EHC, 1,188 (92.9%) received EBRT only, while 91 (7.1%) received both EBRT and brachytherapy. Patients receiving combined modality radiation therapy were more likely to be treated prior to the year 2000. Median overall survival for patients receiving EBRT and EBRT plus brachytherapy was 9 and 11 months, respectively (P=0.04). Cause specific survival was 12 months for those receiving EBRT only, and 15 months for those who received EBRT + brachytherapy (P=0.10). Survival analysis performed on patients with locoregional disease only revealed a trend towards prolonged overall survival with those receiving EBRT + brachytherapy (P=0.08). Multivariate analysis revealed grade and stage of disease were correlated with both overall survival and cause specific survival (P≤0.05). Conclusions: Among patients with unresectable EHC, the addition of brachytherapy to EBRT is associated with a prolonged median overall survival. However, the use of brachytherapy boost decreased in the last decade of the study.